The impact of chorionicity on maternal and fetal outcomes - Bivar, Leonor; Casteleiro, Maria; Vasconcelos, Rita; Borges, Ana; Abreu, Cátia; Reis, Isabel; Sousa-Santos, Ricardo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Women carrying twin pregnancies receive extensive antenatal counselling on fetal risks, but less is known about whether the presence of two placentas confers dissimilar maternal risks. We pretend to determine the impact of chorionicity on the maternal and fetal outcome, evaluating the possibility of finding the association between complications and the presence of two placental masses. Methods: We conducted a retrospective observational cohort study of 550 twin pregnancies monitored at a level-3 hospital, between January 2004 and December 2018. Results: Of the 550 pregnancies, 419 (76.2%) were bichorionic and 131 (23.8%) were monochorionic. Caesarean delivery was more frequent in monochorionic group (70.2% vs. 61.8%, p=0.05). There were no statistically significant differences in the proportion of adverse maternal outcomes between bichorionic and monochorionic pregnancies, despite a trend towards higher proportions in bichorionic group. Regarding fetal outcomes, monochorionic twins were delivered earlier (mean gestational age of 34+4 weeks vs. 35+1 weeks, p=0.04) and the proportion of preterm delivery cases between 32+0 and 36+6 weeks was higher in monochorionic pregnancies (72.5% vs. 54.9%, p=0.002). Stillbirth of one or both twins was more frequent in monochorionic group (3.1% vs. 0.5%, p=0.03). Conclusions: The presence of two placental masses does not seems to confer an increase in maternal risks, despite a trend towards higher proportions of adverse outcomes in bichorionic pregnancies. However, monochorionicity is associated with an increase in fetal risks, particularly prematurity. Counselling and monitoring of bichorionic or monochorionic pregnancies may be identical with respect to maternal risks, but chorionicity should be considered when evaluating fetal risks.